GENETIC CONTROL OF ANTHOCYANIN COLORATION IN RYE - A. V. Voylokov; A. N. Lykholay; V. G. Smirnov (Вавиловский журнал генетики и селекции, 2015)
The authors present their own and literature data on the genetic control of anthocyanin coloration in rye. The concept of the norm for traits of anthocyanin coloration of rye plants is formulated. The analysis of the variability of these traits in inbred lines of winter rye revealed variability in the expression of anthocyanin color in different organs of the plant, which is largely influenced by the environment. For this reason, genetic analysis was performed only for traits with stable manifestation. Six recessive genes vi1–vi6 were identified, whose homozygous state led to the absence of anthocyanin from the whole plant. Of them, only vi1 was localized and mapped on chromosome 7R. The dominant Vs gene for purple pericarp was mapped on chromosome 2R, and one of two complementary genes for red leaf auricle R1, on chromosome 5R. Data from the literature on the identification and localization of anthocyanin coloration genes in rye are discussed in connection with the prospects for further research in this direction.